Evaluasi Kinerja Aset Fasilitas Kawasan Wisata Alam Wayang Windu Panenjoan Pangalengan Kabupaten Bandung - Fadjarwati, Nurlaila; Fadillah, Refa Ardian (Jurnal Ilmiah Pariwisata, 2022)
The Wayang Windu Panenjoan Nature Tourism Area is located within the plantation area of ​​PT Perkebunan Nusantara which is located in Banjarsari Village, Pangalengan District, Bandung Regency, West Java. The total area of ​​this tourist area is only about 832.5 square meters. The hallmark of this tour is the beautiful scenery with the cool air amidst the expanse of tea plantations. The research was conducted to determine the performance of Wayang Windu Panenjoan natural tourism facilities assets as tourism potential in the Pangalengan area, based on two dimensions, namely Main Facilities and Support Facilities. Descriptive research methods with qualitative and quantitative approaches are the basis of the research methods used. The data collection techniques used were observation, interviews, questionnaires, and documentation studies. The result is that there are problems with the performance of the Wayang Windu Nature Tourism Area Facility Assets such as the absence of accommodation, unvaried restaurants, toilet conditions that are still not available. In addition, information center facilities are inadequate, parking spaces are inadequate, prayer equipment is inadequate, facilities for persons with disabilities are not available, and the number of organic and non-organic waste bins is only one. Keywords: Asset Performance, Main Facilities, Support Facilities